Tetra-mu-acetato-kappa O-8:O `-bis{[4-methyl-2-(m-tolylamino)pyridine-kappa N]copper(II)} - Fairuz, Z.A.; Aiyub, Z.; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2010)
In the crystal structure of the title binuclear complex, [Cu-2(CH3COO)(4)(C13H14N2)(2)], the four acetate groups each bridge a pair of Cu-II atoms. The coordination of the metal atoms is distorted square-pyramidal, with the bonding O atoms comprising a square basal plane and the coordinating N atom of the N-heterocycle occupying the apical position. In the two N-hetercycle ligands, the benzene rings are twisted with respect to the pyridine rings, making dihedral angles of 53.1 (2)and 54.2 (2)degrees. Intramolecular N-H center dot center dot center dot O hydrogen bonding is present between the imino and carboxy groups. The crystal studied was a non-merohedral twin with a minor twin component of 21.4%.